SECURITY THREAT ANALYSIS IN CLOUD COMPUTING - Iqbal Fadillah, Muhammad; Irvan Zidni, Mohamad; Adrian Maulana, Riko; Halim Anshor, Abdul (Institut Teknologi Nasional Malang, 2025)
Cloud computing provides significant benefits such as scalability, cost efficiency, and flexibility in accessing computing resources. However, its adoption introduces critical security challenges for organizations, necessitating a thorough analysis of associated risks. This research identifies and categorizes the primary security threats in cloud computing, including data loss, data leakage, cyberattacks, and unauthorized access, and evaluates their impact on organizational operations, data security, and regulatory compliance, with a focus on the financial and healthcare sectors. The study reveals that cyberattacks are the most prevalent and disruptive threat, while data leakage leads to significant legal repercussions and loss of trust. Practical recommendations include adopting encryption, multi-factor authentication, and strict access controls, as well as complying with industry standards like PCI DSS for finance and HIPAA for healthcare. Additionally, a comprehensive risk management framework comprising risk identification, assessment, mitigation, and continuous monitoring is proposed to enhance organizational resilience. By implementing these strategies, organizations can securely leverage cloud computing, maintain regulatory compliance, protect sensitive data, and uphold customer trust